PENINGKATAN HASIL BELAJAR IPA MELALUI MODEL PEMBELAJARAN TGT BERBANTUAN MEDIA LEAFLET DILENGKAPI QUESTION BOX DI SMP NEGERI 1 PAHUNGA LODU - Wori Hana, Ester; Makaborang, Yohana; Djoeroemana, Yohana (Jurnal Biogenerasi, 2024)
This study is a classroom actio research aimed at describing students' cognitive and affective learning outcomes and the improvement in these outcomes at SMPN 1 Pahunga Lodu after applying the TGT model (Teams-Games-Tournament) supported by leaflet media and complemented by a Question Box. The research data were collected from questionnaires, interviews, and learning tests from students.The results of the study on the improvement in student learning outcomes are as follows: Pre-Cycle:Affective: High rating at 0%, medium rating at 26.67%, and low rating at 73.33%.Cognitive: 50% passed and 50% did not pass.Cycle I:Affective: High rating for 8 students (25%), medium rating for 18 students (56.25%), and low rating for 6 students (16.75%).Cognitive: 50% passed, and 50% did not pass.Cycle II:Affective: High rating at 90.62%, medium rating at 9.37%, and low rating at 0%. Cognitive: 80% passed, and 20% did not pass.It can be concluded that the application of the TGT model supported by leaflet media and complemented by a Question Box can improve students' cognitive and affective learning outcomes in science subjects.